2018
DOI: 10.1111/acem.13404
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Diagnostic Testing in the Emergency Department: A Cross‐sectional Study

Abstract: In this ED-based study, patient preferences for diagnostic testing differed significantly across levels of risk, benefit, and cost of diagnostic testing. Cost was the strongest and most consistent factor associated with decreased desire for testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
(13 reference statements)
2
11
0
Order By: Relevance
“…While there is evidence to suggest that patients are financially motivated when making decisions regarding their medical care, how patients respond to payments incentivizing healthy behaviors and decisions remains highly controversial. [6][7][8][9][10] We hypothesized, consistent with the results of our previous study, that patients will be significantly deterred from accepting a low-value head CT scan when a financial incentive to forego lowvalue testing is applied, whereas test risk and benefit will not have a statistically significant effect. 7…”
supporting
confidence: 54%
See 2 more Smart Citations
“…While there is evidence to suggest that patients are financially motivated when making decisions regarding their medical care, how patients respond to payments incentivizing healthy behaviors and decisions remains highly controversial. [6][7][8][9][10] We hypothesized, consistent with the results of our previous study, that patients will be significantly deterred from accepting a low-value head CT scan when a financial incentive to forego lowvalue testing is applied, whereas test risk and benefit will not have a statistically significant effect. 7…”
supporting
confidence: 54%
“…11,12 These values were previously used in an earlier study performed by the authors and were originally selected based on a separate preliminary study performed by the authors, as these values for risk, benefit, and cost were thought to represent the most interesting zone of variation in patients' preferences for diagnostic testing. 6,7 Additionally, values of 0.1 and 1% represent plausible benefit and risk probabilities associated with diagnostic head CT scans following situations of minor head trauma. 13…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased benefit of testing (ie, finding nonsurgical lesions) and increased cost have been associated with decreased patient preference for head CT. 4 Most patients prefer to discuss CT radiation risk. 5 And as the probability of life-threatening injury decreases, fewer patients choose to undergo CT 5 ; when presented with a life-threatening injury threshold of 2%, 34% 2 to 54% 5 of patients may decide to forgo CT.…”
Section: Abandoning Further Study Of the Application Of Computed Tomomentioning
confidence: 99%
“…2 From a contextual standpoint, the results discussed by Wright et al tend to confirm research that postulates that context has a major influence on decisionmaking. 3,4 The heuristics used by emergency physicians included in the study to manage patients with abdominal pain would thus likely be very different in other, less acute contexts of medical practice. The authors have shown that these mechanisms are above all intuitive and therefore irrepressibly mobilized, which demonstrates the very high level of internalization of the specificities and requirements linked to the context; in this case, in regard to the need for risk stratification in emergency departments.…”
Section: Decisionmaking In Emergency Medicine: Experienced-based and mentioning
confidence: 99%